Holocene occupation history of pygoscelid penguins at Stranger Point, King George (25 de Mayo) Island, northern Antarctic Peninsula - Emslie, Steven Douglas (2019)
We report additional fossil evidence for pygoscelid penguins breeding on King George (25 de Mayo) Island, South Shetland Islands, in the Holocene beginning at ~7000 cal. yr BP. This evidence comes from a raised marine beach deposit formerly studied and described as Pingfo I at Stranger Point, Potter Peninsula. We relocated and exposed deposits at this site and recovered additional samples of penguin bones from five stratigraphic beds that are redescribed here. Most of these bones are from juvenile penguins and exhibit little or no wear indicating minimal transport to the beach deposits. Some of the bones are developed enough to be identifiable to Adélie (Pygoscelis adeliae), Gentoo (Pygoscelis papua), and Chinstrap (Pygoscelis antarctica) penguins, indicating that all three species were breeding at Stranger Point from ~7320 to 4865 cal. yr BP. This breeding occupation corresponds with the first warming and deglaciation that occurred in the northern Antarctic Peninsula by this time and ends with the onset of reglaciation of the Peninsula. At least 31 abandoned penguin mounds and ornithogenic soils also were located and sampled at Stranger Point and indicate that the current occupation of this area by all three pygoscelid penguins dates no older than ~535 cal. yr BP. The absence of ornithogenic soils from earlier Holocene breeding was probably due to glacial activity and soil solifluction during periods of warming in the mid to late Holocene.